PREVALENCE OF ENTEROBIUS VERMICULARIS (PINWORM) AMONG PRIMARY SCHOOL BOYS IN SELECTED VILLAGES OF MISAN GOVERNORATE, SOUTHERN IRAQ - Abul-Doanej, Hasan Azaati Ibadi (Journal of Medical Genetics and Clinical Biology, 2026)
Objective: This study aimed to determine the prevalence of Enterobius vermicularis (pinworm) infection among male primary school pupils in selected rural villages in Misan Governorate, Iraq, and to examine age-related infection patterns as well as the health and environmental factors contributing to its transmission. Method: A total of 384 schoolchildren aged 7–13 years were surveyed between 25 February and 30 April 2025. Stool samples were collected and examined using the wet-mount normal saline technique to detect intestinal parasites, with a specific focus on E. vermicularis. Results: Parasitological analysis identified 43 infections (11.2%), including 26 cases of E. vermicularis (6.77%), 8 cases of Entamoeba histolytica (2.08%), and 9 cases of Giardia lamblia (2.34%), with no mixed infections recorded. The highest prevalence of E. vermicularis occurred among 7-year-olds (42.9%), while the lowest (3%) appeared in the 11–12 age groups. Infection rates decreased progressively with age, except for a slight increase at age 13 (9%), with differences statistically significant (P ≤ 0.05). Novelty: This study provides updated epidemiological evidence from understudied rural communities in Misan Governorate, emphasizing the continuing public health burden of enterobiasis and the need for targeted hygiene-focused interventions.